Life-cycle bias and the returns to schooling in current and lifetime earnings - Manudeep Bhuller; Magne Mogstad; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2011)
This paper uses a unique data set with nearly career-long earnings histories to provide evidence on the returns to schooling in current and lifetime earnings. We use these results to assess the importance of life-cycle bias in earnings regressions using current earnings as a proxy for lifetime earnings. To account for the endogeneity of schooling, we apply three commonly used identification strategies. Our estimates demonstrate a strong life-cycle bias, often exceeding the bias from assuming that schooling is exogenous. We further explore the problems caused by life-cycle bias in research on the economic returns to schooling, and discuss possible remedies.
urn:nbn:de:101:1-201106224681
Keywords: J24; J31; 330; returns to schooling; life-cycle bias; lifetime earnings; current earnings; errors-in-variables model